Near-Infrared Light Responsive Nanoreactor for Simultaneous Tumor Photothermal Therapy and Carbon Monoxide-Mediated Anti-Inflammation - Wang, Shi-Bo; Zhang, Cheng; Ye, Jing-Jie; Zou, Mei-Zhen; Liu, Chuan-Jun; Zhang, Xian-Zheng (ACS central science, 2020)
Photothermal therapy (PTT) is an effective treatment modality with high selectivity for tumor suppression. However, the inflammatory responses caused by PTT may lead to adverse reactions including tumor recurrence and therapeutic resistance, which are regarded as major problems for PTT. Here, a near-infrared (NIR) light-responsive nanoreactor (P@DW/BC) is fabricated to simultaneously realize tumor PTT and carbon monoxide (CO)-mediated anti-inflammatory therapy. Defective tungsten oxide (WO3) nanosheets (DW NSs) are decorated with bicarbonate (BC) via ferric ion-mediated coordination and then modified with polyethylene glycol (PEG) on the surface to fabricate PEG@DW/BC or P@DW/BC nanosheets. Upon 808 nm NIR laser irradiation, the DW content in P@DW/BC can serve as not only a photothermal agent to realize photothermal conversion but also a photocatalyst to convert carbon dioxide (CO2) to CO. In particular, the generated heat can also trigger the decomposition of BC to produce CO2 near the NSs, thus enhancing the photocatalytic CO generation. Benefiting from the efficient hyperthermia and CO generation under single NIR laser irradiation, P@DW/BC can realize effective thermal ablation of tumor and simultaneous inhibition of PTT-induced inflammation.